2013 6th International IEEE/EMBS Conference on Neural Engineering (NER) 2013
DOI: 10.1109/ner.2013.6696078
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned behavior in a robot controlled by a spiking neural network

Abstract: Insects show a rich repertoire of goal-directed and adaptive behaviors that are still beyond the capabilities of today's artificial systems. Fast progress in our comprehension of the underlying neural computations make the insect a favorable model system for neurally inspired computing paradigms in autonomous robots. Here, we present a robotic platform designed for implementing and testing spiking neural network control architectures. We demonstrate a neuromorphic realtime approach to sensory processing, rewar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Milde et al (2017) performed obstacle avoidance and target acquisition tasks with a robotic vehicle, on which an SNN takes event-based vision sensor as the input and runs on a neuromorphic hardware. It is worth mentioning that some fixed SNN architectures aim at solving a problem by imitating parts of structures of natural neural networks found in living organisms such as the withdrawal circuit of the Aplysia—a marine snail organism—in Alnajjar et al (2008), olfactory learning observed in the fruit fly or honey bee in Helgadottir et al (2013), or the cerebellum in Carrillo et al (2008).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Milde et al (2017) performed obstacle avoidance and target acquisition tasks with a robotic vehicle, on which an SNN takes event-based vision sensor as the input and runs on a neuromorphic hardware. It is worth mentioning that some fixed SNN architectures aim at solving a problem by imitating parts of structures of natural neural networks found in living organisms such as the withdrawal circuit of the Aplysia—a marine snail organism—in Alnajjar et al (2008), olfactory learning observed in the fruit fly or honey bee in Helgadottir et al (2013), or the cerebellum in Carrillo et al (2008).…”
Section: Related Workmentioning
confidence: 99%
“…Each output neuron represented a different movement direction. In other approaches, such as Helgadottir et al (2013) or Spüler et al (2015), only a limited amount of synaptic connections employ synaptic plasticity while the majority of the synaptic strengths were fixed. Unfortunately, similar approaches only work for simple tasks rather than more complex tasks, which require precise tuning of many more degrees of freedom, e.g., one or more hidden layers, to solve the given task with satisfactory precision.…”
Section: Related Workmentioning
confidence: 99%
“…Non-evolutionary approaches to spiking robot control include dynamic learning of navigation behaviour via conditioning (Helgadottir et al, 2013) and real-time training of neuro-controllers based on resovoir computing (Burgsteiner, 2005). Wiles et al (2010) creates biologically plausible models of a rat's brain via self-organised learning for phototaxis.…”
Section: Background Spiking Neuro-controllersmentioning
confidence: 99%
“…Neuromorphic computing [1] is a novel paradigm that aims at emulating the naturalistic, flexible structure of animal brains on an analogous physical substrate with the potential to outperform von Neumann architectures in a range of real-world tasks [2, 3]. It can inspire novel AI solutions [4–6] and may support control of autonomous agents by spiking neural networks [7–9]. A major challenge for brain-inspired neuromorphic solutions is the identification of computational principles and circuit motifs in animal nervous systems that can be utilized on neuromorphic hardware to exploit its benefits.…”
Section: Introductionmentioning
confidence: 99%